The effect of a pulsating spraying jet on the volume of air that comes in contact with metal electrodes during arc metallization. - , Iryna Zakharova (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
At electroarc spraying, there is intensive oxidation of the sprayed metal due to oxygen of the air, which leads to a significant decrease of the content of alloying elements in the coating and, accordingly, deteriorates the quality of the sprayed layer. This issue was brought to light by the authors of scientific publications that proposed the use of kerosene, propane and air mixture, inert gases as a transportation gas, but these solutions led to a significant increase in the cost of the arc metalization process, and often had no quantitative calculations of the impact on the quality of coatings or were approximate. The purpose of this paper is to provide a scientific justification for the concept of improving the quality of coatings by reducing the negative impact of oxygen of the air during arc metallization by using a pulsating spraying air jet. This paper presents a mathematical analysis of determining the amount of air at the formation of a controlled pulsating spraying airflow with specific pulses at arc metallization. The results of the research have shown that the use of a pulsating air spraying flow at the application of coatings by arc metallization will reduce the burnout of alloying elements in the applied coating, which will improve the quality of the restored parts